1999
DOI: 10.1111/j.1365-2621.1999.tb12289.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Pathogens Using Hot Water and Lactic Acid on Beef Trimmings

Abstract: Beef trimmings from young or mature beef cattle were obtained commercially. Trimmings within age type then were inoculated with about 6.0 log 10 CFU/mL of rifampicin-resistant. Escherichia coli O157:H7 and Salmonella typhimurium (ATCC 13311) were randomly assigned to 1 of 3 treatments (control; 95 °C hot water alone, or with 2% L-lactic acid). After treatment, trimmings were ground, held for 0, 14, 28, or 42 d in chub packages at 4 °C, and total aerobic plat counts, E. coli O157:H7, and S. typhimurium counts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 13 publications
3
27
1
Order By: Relevance
“…On day 5 of refrigerated storage larger reduction levels were observed especially for fifth, sixth and seventh group. Similar results were observed by Ellebracht, Castillo, Lucia, Miller, and Acuff (1999) who reported 0.7 log reductions of S. Typhimurium using HW (95°C, 3 s) decontamination of beef trimmings. Reagan et al (1996) observed 2.0-1.8 log reductions of aerobic plate counts and generic E. coli counts on beef carcasses using HW spray-washing treatments (74-87.8°C, 11-18 s, 1310-2413 kPa), which may show the antimicrobial effects of HW treatments on beef carcasses.…”
Section: Resultssupporting
confidence: 91%
“…On day 5 of refrigerated storage larger reduction levels were observed especially for fifth, sixth and seventh group. Similar results were observed by Ellebracht, Castillo, Lucia, Miller, and Acuff (1999) who reported 0.7 log reductions of S. Typhimurium using HW (95°C, 3 s) decontamination of beef trimmings. Reagan et al (1996) observed 2.0-1.8 log reductions of aerobic plate counts and generic E. coli counts on beef carcasses using HW spray-washing treatments (74-87.8°C, 11-18 s, 1310-2413 kPa), which may show the antimicrobial effects of HW treatments on beef carcasses.…”
Section: Resultssupporting
confidence: 91%
“…These characteristics favor their use in meat products. Several studies have tested the efficacy of organic acids (Castillo, Lucia, Goodson, Savell, & Acuff, 1998Castillo, Lucia, Mercado, & Acuff, 2001;Ellebracht, Castillo, Lucia, Miller, & Acuff, 1999;González-Fandos, Herrera, & Maya, 2009;Over, Hettiarachchy, Johnson, & Davis, 2009;Tamblyn & Conner, 1997a, 1997bThomson, Banwart, Sanders, & Mercuri, 1967) but sensory changes (color and flavor) might be taken in consideration. Organic acids and their salts are considered weak acids, meaning they do not fully dissociate in water but do so in a pH-dependent manner.…”
Section: Organic Acids In Meat Productsmentioning
confidence: 99%
“…Acceptable daily intake for humans is exhibited in Table 2. Its use in the meat industry is widespread and many researchers have documented its efficacy for the reduction of enteric pathogens on the surfaces of carcasses and derived cuts (Baird, Lucia, Acuff, Harris, & Savell, 2006;Bosilevac, Nou, Barkocy-Gallagher, Arthur, & Koohmarie, 2006;Castillo et al, 2001;Castillo, Lucia, Goodson, Savell, & Acuff, 1998Delmore et al, 2000;Dixon, Vanderzant, Acuff, Savell, & Jones, 1987;Ellebracht et al, 1999).…”
Section: Lactic Acid and Lactatesmentioning
confidence: 99%
“…However, the treatment was less effective on beef inside rounds because of the surface variation, where bacteria could become embedded or attached and not receive sufficient contact by the sprays (9). A similar situation was reported by Ellebracht et al (6) when a 3-s hot water treatment (95 °C) was used to treat beef trimmings. Researchers noted that not all of the fat and lean surfaces were evenly exposed to treatment because of overlap and thus, treatment was not consistently effective (6).…”
Section: Resultsmentioning
confidence: 58%